An Analysis of the Romanian General Accounting Plan. Opportunities for Adaptation to the Activity-Based Costing (ABC) Method - Irina-Alina Preda; Sorinel Capusneanu (Theoretical and Applied Economics, 2008)
In this article, we analyze the causes that have led to the improvement of the Romanian general accounting plan according to the Activity- Based Costing (ABC) method. We explain the advantages presented by the dissociated organization of management accounting, in contrast with the tabular- statistical form. The article also describes the methodological steps to be taken in the process of recording book entries, according to the Activity-Based Costing (ABC) method in Romania.